2017
DOI: 10.1002/sia.6290
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the preparation conditions ofPd‐ZrO2andAuPd‐ZrO2nanoparticle–decorated functionalisedMWCNTs: Electron spectroscopy study aided with theQUASES

Abstract: The Pd, AuPd, and ZrO2 nanoparticle–decorated functionalised multiwalled carbon nanotubes (f‐MWCNTs) were reported as efficient catalysts of formic acid (FA) electro‐oxidation. Different preparation conditions influence their chemical and structural properties analysed by X‐ray photoelectron spectroscopy aided with the quantitative analysis of surfaces by electron spectroscopy. Different reduction procedures such as NaBH4, a polyol microwave‐assisted method (PMWA), and a high pressure microwave reactor (HPMWR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…For the example used in this paper, the universal cross‐section was utilized in all instances for the analysis of Cr and Mo peaks. The universal cross‐section has been proven to describe the cross‐section for most metals and their respective oxides with sufficient accuracy 41 and has been utilized in many studies 19,22,48,49 . For other solids (i.e., Al, Si, SiO 2 , Ge, and polymers), an alternative cross‐section is required to describe the electron energy loss processes accurately.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the example used in this paper, the universal cross‐section was utilized in all instances for the analysis of Cr and Mo peaks. The universal cross‐section has been proven to describe the cross‐section for most metals and their respective oxides with sufficient accuracy 41 and has been utilized in many studies 19,22,48,49 . For other solids (i.e., Al, Si, SiO 2 , Ge, and polymers), an alternative cross‐section is required to describe the electron energy loss processes accurately.…”
Section: Resultsmentioning
confidence: 99%
“…The universal cross-section has been proven to describe the cross-section for most metals and their respective oxides with sufficient accuracy 41 and has been utilized in many studies. 19,22,48,49 For other solids (i.e., Al, Si, SiO 2 , Ge, and polymers), an alternative cross-section is required to describe the electron energy loss processes accurately. Using the reflected electron energyloss spectroscopy (REELS) method of cross-section determination, Tougaard demonstrated that the cross-section for Si has a distinct plasmon peak at 16.8 eV.…”
Section: Inelastic Background Signal Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the BE values increased for carbon nanostructures that contained electron-withdrawing groups such as defects (like pentagons and hexagons) and hydrogen [66][67][68][69]. The experiments conducted on various carbon nanomaterials revealed a separation value in the binding energy (BE) between C sp 2 and C sp 3 , which ranged from 0.6 eV to 1.35 eV [66,[70][71][72]. Diamond-like carbon (DLC) films were reported to have binding energy (BE) values of 0.6 eV [73] and 0.8 eV [70].…”
Section: Resultsmentioning
confidence: 99%